A chromatin modifier integrates insulin/IGF‐1 signalling and dietary restriction to regulate longevity. Issue 4 (2nd April 2016) - Singh, Anupama; Kumar, Neeraj; Matai, Latika; Jain, Vaibhav; Garg, Amit; Mukhopadhyay, Arnab
Summary: Insulin/IGF‐1‐like signalling (IIS) and dietary restriction (DR) are the two major modulatory pathways controlling longevity across species. Here, we show that both pathways license a common chromatin modifier, ZFP‐1/AF10. The downstream transcription factors of the IIS and select DR pathways, DAF‐16/FOXO or PHA‐4/FOXA, respectively, both transcriptionally regulate the expression of zfp‐1 . ZFP‐1, in turn, negatively regulates the expression of DAF‐16/FOXO and PHA‐4/FOXA target genes, apparently forming feed‐forward loops that control the amplitude as well as the duration of gene expression. We show that ZFP‐1 mediates this regulation by negatively influencing the recruitment of DAF‐16/FOXO and PHA‐4/FOXA to their target promoters. Consequently, zfp‐1 is required for the enhanced longevity observed during DR and on knockdown of IIS. Our data reveal how two distinct sensor pathways control an overlapping set of genes, using different downstream transcription factors, integrating potentially diverse and temporally distinct nutritional situations.